The Cotingo Dam as a test of Brazil's system for evaluating proposed developments in Amazonia - Fearnside, Philip Martin; Barbosa, Reinaldo Imbrozio (Environmental Management, 1996)
The proposed Cotingo Dam in Brazil's far northern state of Roraima is examined with the objective of drawing lessons for Brazil's system of evaluating environmental, social, and financial consequences of development decisions. The Cotingo Dam illustrates the difficulty of translating into practice the principles of economic and environmental assessment. Examination of the financial arguments for the Cotingo Dam indicates that justifications in this sphere are insufficient to explain why the project is favored over other alternatives and points to political factors as the best explanation of the project's high priority. Strong pressure from political and entrepreneurial interest groups almost invariably dominates decision making in Amazonia. The analysis indicates the inherent tendency of the present system to produce decisions in favor of large construction projects at the expense of the environment and local peoples. The requirements intended to assure proper weight for these concerns, such as the report on environmental impacts (RIMA) and the public hearing, fail to serve this role. Cotingo also provides a test case for constitutional protections restricting construction of dams in indigenous lands.
Keywords: Brasil; Decision Making; Environmental Impact Assessment; Environmental Management; Industrialization; Review; Socioeconomics; Construction; Dams; Decision Making; Economic And Social Effects; Finance; Hydroelectric Power; Laws And Legislation; Project Management; Brasil; Development Projects; Hydroelectric Dams; Indigenous Peoples; Political Factors; Rainforest; Environmental Impact; Dam Construction; Decision Making; Developing Country; Development Planning; Environmental Assessment; Environmental Impact; Hydropower Project; Planning Practice; Political Context; Social Impact; Brazil, Roraima State, Cotingo Dam